STRATEGI KOMUNIKASI PEMASARAN PADA MEDIA DAKWAH LPD AL BAHJAH DALAM MENGEMBANGKAN MEDIA MASSA DARING - Matin, Nasrudin Abdul (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2017)
The objectives of this research are as follows: (1). To find out the marketing communication activities in Al-Bahjah Media. (2). To know the process of Al-Bahjah Media, in advertising marketing to the public. (3). To find out the strategy of building online media by Media Al Bahjah in advertising. A mature concept, as found by Media Da'wah Al Bahjah TV in its strategy to find 2 steps that must be carried out including: First, mastering this market segmentation is one strategy to understand the market structure by grouping consumers or partnering with our institutions. Or make a media father. Second, the da'wah media must have strong and istiqomah principles, one of which is al-bahjah's da'wah media has rules, conditions or its name is manhajiah, which contains provisions for maintaining sharia.